Thực hiện các phép tính :
a) \((2 + 4i)(3 - 5i) + 7(4 - 3i)\)
b) \((1 - 2i)2 - (2 - 3i)(3 + 2i)\)
a)
\left( {2 + 4i} \right)\left( {3 - 5i} \right) + 7\left( {4 - 3i} \right)\\
= 6 - 10i + 12i - 20{i^2} + 28 - 21i\\
= 6 + 2i + 20 + 28 - 21i\\
= 54 - 19i
\end{array}\)
b)
{\left( {1 - 2i} \right)^2} - \left( {2 - 3i} \right)\left( {3 + 2i} \right) = 1 - 4i + 4{i^2} - \left( {6 + 4i - 9i - 6{i^2}} \right)\\
= 1 - 4i - 4 - 6 + 5i - 6 = - 15 + i
\end{array}\)
-- Mod Toán 12
Copyright © 2021 HOCTAP247